OBSERVATION ON BEACH EROSION AND CORAL DESTRUCTION BY REMOTE SENSING TECHNIQUES - Praseno, Djoko P.; Sukarno, - (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1977)
Remote sensing techniques were used to observe beach erosion at Sengkidu Beach, Labuan Amuk, east coast of Bali. Erosion was caused by wave actions flowing over destructed coral reef. Aerial photography was found useful in obtaining first hand information of the destructed corals and its affects on the beach.